Some properties of a model F1 layer of the ionosphere - De Jager, Gerhard (Rhodes University, Faculty of Science, Department of Physics, 1963)
The present work was initially aimed at providing an explanation for some of the phenomena that occur in the ionosphere at sunrise. The approach that was taken was to determine the changes that take place on a theoretical model of the ionosphere and then to compare these with observations. A prerequisite for this approach was a theoretical model that would show, among other things, a bifurcation of the F layer during daytime without making unjustified arbitrary assumptions. The absence of such a model, particularly as far as non-equilibrium conditions are concerned, resulted in the present attempt to provide such a model for the F1 region.
Keywords: Ionosphere; Ionospheric electron density